2017
DOI: 10.3892/ijmm.2017.3269
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30a‑5p suppresses tumor cell proliferation of human renal cancer via the MTDH/PTEN/AKT pathway

Abstract: The present study aimed to explore the effects of microRNA (miRNA)‑30a‑5p on tumor proliferation and to seek a potential therapeutic target for the treatment of human renal cancer. The results demonstrated that the expression levels of miRNA‑30a‑5p were reduced in tumor samples from patients with renal cancer compared with in normal tissue samples. Overall survival and disease‑free survival were increased in patients with renal cancer and high miRNA‑30a‑5p expression compared with in those with low miRNA‑30a‑5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…PTEN was the target of miR-28 and suppressed gastric cancer cell proliferation and invasion (41). Additionally, it suppressed renal cancer cell proliferation as a target of miR-30a (42). Zhao et al reported that PTEN regulated OS cell growth and apoptosis and acted as a target of miR-19 (43).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN was the target of miR-28 and suppressed gastric cancer cell proliferation and invasion (41). Additionally, it suppressed renal cancer cell proliferation as a target of miR-30a (42). Zhao et al reported that PTEN regulated OS cell growth and apoptosis and acted as a target of miR-19 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Highly expressed MTDH was reported to serve important roles in the onset and the progression of OSCC by affecting tumor cell growth, colony formation, migration and invasion (26,28,29). MTDH has previously been reported to be involved in the regulation of the PTEN/AKT signaling pathway (23,24). It has been well established that activation of the PTEN/AKT pathway contributes to OSCC development (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experiments were performed to determine whether MTDH was a direct target gene of miR-655 in OSCC cells. MTDH has previously been reported to contribute to the regulation of the phosphatase and tensin homolog (PTEN)/protein kinase (AKT) signaling pathway (23,24); therefore, the present study also investigated whether miR-655 participated in the regulation of the PTEN/AKT signaling pathway in OSCC cells.…”
Section: Microrna-655 Suppresses Cell Proliferation and Invasion In Omentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that MTDH is expressed in almost all malignant tumor cells. MTDH overexpression can enhance the proliferation, differentiation, metastasis and invasion capacity of endometrial cancer, prostate cancer, breast cancer and human glioma cells (18). In addition, MTDH plays a key role in upregulating tumor genesis mediated by the Ha-as oncogene (19).…”
Section: Discussionmentioning
confidence: 99%